Analisis Pengendalian Kualitas Produksi Di Pt. Masscom Graphy Dalam Upaya Mengendalikan Tingkat Kerusakan Produk Menggunakan Alat Bantu Statistik - Radeya Khaliq; Qazi Najah (Yayasan Gema Bina Nusantara, 2023)
The role of quality cost control is very important to ensure that all company activities can run smoothly, especially in carrying out the production process and are expected to improve quality so that really good output is obtained, so as to suppress or reduce the number of damaged products. Because if in the production process there are many damaged products, the company will experience losses caused by the large amount of costs, labor and time spent because of these damaged products. With the issuance of quality costs, it is expected to reduce losses caused by damaged products.